2011
DOI: 10.1111/j.1468-3083.2011.04041.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tumour necrosis factor‐α antagonists in aphthous ulceration: review of published individual patient data

Abstract: Evidence for efficacy of TNF-α antagonists in aphthous ulceration infection is limited. Such data suggest that in patients with severe aphthous ulceration TNF-α antagonists have some efficacy in inducing ulcer resolution and reducing recurrence. These agents may represent an option in severe refractory aphthosis, although in the absence of controlled studies, caution is advocated if use is to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The response rate to TNF‐alpha inhibitors was almost 90% in patients presenting with recurrent oral and/or genital aphthosis who were otherwise unresponsive or intolerant to recommended systemic therapy. We and others have previously published patient series and case reports demonstrating efficacy of TNF‐alpha inhibitors in patients with primary complex aphthosis, but the 26 patients in this study comprise the so far largest group of patients treated with TNF‐alpha inhibitors . TNF‐alpha has been found to trigger inflammation, clinical manifestations, and recurrence of aphthous stomatitis in patients with Behcet's disease, which may explain the high response rate of TNF‐alpha inhibitors in our patients with primary complex aphthosis .…”
Section: Discussionmentioning
confidence: 87%
“…The response rate to TNF‐alpha inhibitors was almost 90% in patients presenting with recurrent oral and/or genital aphthosis who were otherwise unresponsive or intolerant to recommended systemic therapy. We and others have previously published patient series and case reports demonstrating efficacy of TNF‐alpha inhibitors in patients with primary complex aphthosis, but the 26 patients in this study comprise the so far largest group of patients treated with TNF‐alpha inhibitors . TNF‐alpha has been found to trigger inflammation, clinical manifestations, and recurrence of aphthous stomatitis in patients with Behcet's disease, which may explain the high response rate of TNF‐alpha inhibitors in our patients with primary complex aphthosis .…”
Section: Discussionmentioning
confidence: 87%
“…Thus, it would appear that TNF‐α inhibitors are effective in inducing resolution in oral aphthous and aphthous‐like ulcers and may be appropriate therapy in those patients in which disease is severe and refractory to, or patients are intolerant of, traditional immunomodulatory regimens (Arida et al , 2011; O’Neill, 2012). Most data are available for infliximab, but no specific agent would appear superior, and switching to an alternative TNF‐α antagonist when no initial response is seen may also be effective (Estrach et al , 2002; Aikawa et al , 2011).…”
Section: Aphthous Ulcerationmentioning
confidence: 99%
“…In another study, Etanercept, a fusion protein of the TNF-α receptor and the Fc portion of human IgG1, had a favorable effect on RAS of the oral cavity. In one review, sixteen patients underwent treatment for refractory or severe aphthous ulcers with tumor necrosis factor alpha antagonists, between 1995 and 2010 [32]. Of the drugs used, infliximab, etanercept and adalimumab appeared to improve outcomes [32].…”
Section: Response Of Aphthous Stomatitis To Diet and Biological Respomentioning
confidence: 99%
“…In one review, sixteen patients underwent treatment for refractory or severe aphthous ulcers with tumor necrosis factor alpha antagonists, between 1995 and 2010 [32]. Of the drugs used, infliximab, etanercept and adalimumab appeared to improve outcomes [32]. Sanchez-Cano et al, also reported improved outcomes with adalimumab in a patients with severe aphthous ulcers [33].…”
Section: Response Of Aphthous Stomatitis To Diet and Biological Respomentioning
confidence: 99%